ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN RUMAH TANGGA BURUH NELAYAN DI DESA DUDEPO KECAMATAN BOLAANG UKI KABUPATEN BOLAANG MONGONDOW SELATAN - Boekoesoe, Yuriko; Imran, Supriyo; Biya, Ferdiyanto (Universitas Negeri Gorontalo, 2024)
This research aimed (1) to determine factors affecting the income of labor fishermen households in Dudepo Village, Bolaang Uki Subdistrict, Bolaang Mongondow Selatan Regency, and (2) to determine the income of labor fishermen household in Dudepo Village, Bolaang Uki Subdistrict, Bolaang Mongondow Selatan Regency. This research was conducted in Dudepo Village, Bolaang Uki Subdistrict, Bolaang Mongondow Selatan Regency, from August to September 2022, with a total sample of 41 labor fishermen. The research method used was the quantitative method, in which the data analysis used was descriptive analysis and multiple linear regression analysis. The research findings signified that (1) the factors affecting income of labor fishermen household were fishing capital, fishing time, and fishing experience where the fishing time was the one with a significant effect on labor fishermen's income. Meanwhile, fishing capital and fishing experience did not indicate any significant effect on labor fishermen's income, and (2) the monthly income of labor fishermen household was an average of IDR. 2.104.878, while the monthly income from non-fisheries sector was an average of IDR. 635.366. Thus, it blatantly denoted that higher income was from the fisheries sector which was the main source of livelihood for fishermen to meet family needs.